Das vergessene Appeasement von 1920 : Lloyd George, Lenin und Polen - Nowak, Andrzej (2024)
The book examines a turning point in European history: the summer of 1920, when Lenin's Soviet Russia decided to launch an attack on the continent. Professor Nowak uses hitherto unexamined documents from Russian and British archives to show how (and why) top British politicians were ready to accept a new Russian imperial control over the whole of Eastern Europe. He unravels this hitherto untold story of that first and forgotten appeasement.